2015
DOI: 10.1186/s12907-015-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of Pap smear cervical epithelial cell abnormality among HIV-positive and negative women attending gynecological examination in cervical cancer screening center at Debre Markos referral hospital, East Gojjam, Northwest Ethiopia

Abstract: BackgroundCervical cancer is the leading cause of cancer related death among women in developing countries. Cervical cancer is preceded by cervical surface epithelial cell abnormalities (ECA) which can be detected by Pap smear test. Simultaneous human papillomavirus and human immunodeficiency virus (HIV) infection increases cervical cancer. Data on the prevalence and predictors of ECA among women in Ethiopia is limited. Hence, we aimed to determine the prevalence and associated factors of ECA among women.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
70
5
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 43 publications
16
70
5
3
Order By: Relevance
“…This was comparable to a study conducted in Cameroun which reported a prevalence of 43.5% [20], further giving credence to the fact that CIN changes are more in patients with HIV infection. Other studies conducted in Nigeria and Ethiopia, however, showed lower prevalence rates [21,22]. The difference in the prevalence rates may be due to the use of cytological smears for the diagnosis of CIN as opposed to histologically confirmed lesions used in this study.…”
Section: Discussionmentioning
confidence: 55%
“…This was comparable to a study conducted in Cameroun which reported a prevalence of 43.5% [20], further giving credence to the fact that CIN changes are more in patients with HIV infection. Other studies conducted in Nigeria and Ethiopia, however, showed lower prevalence rates [21,22]. The difference in the prevalence rates may be due to the use of cytological smears for the diagnosis of CIN as opposed to histologically confirmed lesions used in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Getinet et al (17) encontraram na Etiópia, em 197 pacientes HIV positivo, 82,2% de amostras negativas, 5,6% de ASCUS, 6,1% de LSIL, 5,1% de HSIL e 1,0% de carcinoma escamoso. Kreitchmann et al, (18) em Porto Alegre, encontraram amostras negativas em 82,5%, ASCUS em 6,2%, LSIL em 8,7%, HSIL em 2,4% e carcinoma invasor em 0,1%, valores semelhantes aos encontrados em nosso estudo, apenas com a diferença de terem encontrado carcinoma epidermoide.…”
Section: Discussionunclassified
“…Em nosso estudo, os resultados encontrados foram semelhantes aos encontrados por Getinet et al, (17) Chalermchockcharoenkit et al, (16) Silva et al, (13) Kreitchmann et al, (16) Brock (17) e Lemos et al (18) Apenas Camargo et al (21) obtiveram índices inferiores de positividade, com maior índice de LSIL e ASCUS em relação aos demais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cervical epithelial cell abnormalities (ECA) can result in cervical cancer which is the most common cause of cancer related death especially in developing countries [2]. Cervical ECA can be detected by Pap smear.…”
Section: Introductionmentioning
confidence: 99%